2000
DOI: 10.1292/jvms.62.65
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Dog Sperm Capacitation by Glycosaminoglycans and Glycosaminoglycan Amounts of Oviductal and Uterine Fluids in Bitches.

Abstract: ABSTRACT. Ejaculated sperm collected from 12 beagle dogs were incubated in canine capacitation medium (CCM), supplemented with 5 µg/ml chondroitin sulfate A (CS), 5 µg/ml hyaluronic acid (HA), or 5 µg/ml heparin (HP) for 7 hr at 38°C in a 5% CO2 in air atmosphere to investigate the effects of glycosaminoglycans (GAGs) on dog sperm capacitation. The percentages of motile sperm, hyperactivated sperm (%HY), and acrosome-reacted sperm (%AR) in all media were examined after 4 hr and 7 hr of incubation. The oviducts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 36 publications
1
34
0
1
Order By: Relevance
“…However, most of the epithelial cells were derived from diestrous bitches, which may well lack the proteins essential for promoting meiotic maturation because oviductal secretory cells are mostly active during estrus (not diestrus). Intraoviductal concentrations of glycosaminoglycans are higher in estrual compared to anestrous bitches (Kawakami et al, 2000). In fact, culturing dog oocytes with oviductal cells recovered from an estrual bitch improved the proportions of oocytes resuming meiosis and developing to the MII stage (Bogliolo et al, 2002;Luvoni et al, 2003).…”
Section: Co-culturementioning
confidence: 95%
“…However, most of the epithelial cells were derived from diestrous bitches, which may well lack the proteins essential for promoting meiotic maturation because oviductal secretory cells are mostly active during estrus (not diestrus). Intraoviductal concentrations of glycosaminoglycans are higher in estrual compared to anestrous bitches (Kawakami et al, 2000). In fact, culturing dog oocytes with oviductal cells recovered from an estrual bitch improved the proportions of oocytes resuming meiosis and developing to the MII stage (Bogliolo et al, 2002;Luvoni et al, 2003).…”
Section: Co-culturementioning
confidence: 95%
“…The high concentration of GAGs during estrum foregrounds the uterus´s macroscopic increase, since these molecules trigger tissue hydration and, at the same time, tissue hyperplasia (Cubas et al 2010). Studies on bitches during the anestrus phases or estrus and the comparison of GAGs rates in the fluids of the ampulla and isthmus of the uterine tubes and the lumen of the uterine horns showed that GAGs concentrations in these organs are greater in the bitches in the estrus when compared to those in the anestrus phase (Kawakami et al 2000). This is due to estrogen on the genital organs during the estrus cycle.…”
Section: Hormonal Influence In Gags Profilementioning
confidence: 99%
“…Une seule publication a trait à la composition du liquide tubaire canin en glycosaminoglycanes et à leur rôle dans la capacitation spermatique (Kawakami et al 2000). Les analyses biochimiques réa-lisées chez la vache , la truie (Buhi et al 1990), montrent que les sécrétions tubaires sont constituées d'un mélange de composés transsudés d'origine sérique et de composés spécifiques sécrétés par l'épithélium tubaire, dont la composition est sensiblement identique dans ces espèces…”
Section: Composition Du Microenvironnement Tubaireunclassified